Solarizing groundwater irrigation in India: a growing debate. Issue 1 (2nd January 2018) - Bassi, Nitin
Abstract: India is on a path to reduce its carbon emission intensity with a major thrust on increasing the grid-connected solar photovoltaic capacity. However, the carbon footprint in agriculture is on the rise. Heavy subsidies for electricity and diesel to pump groundwater for irrigated agriculture, combined with lack of regulations on water withdrawal, are resulting in both groundwater over-exploitation and increased carbon emissions. Some researchers and practitioners have suggested large-scale promotion of solar pumps for well irrigation as a way to make agricultural growth carbon-neutral and groundwater use in farming sustainable. This article examines whether solar pumps for groundwater irrigation are technically feasible and economically viable in India.